Case Report: Multiple primary bilateral lung benign notochord cell tumors combined with sacral tumors - Tao, Minjia; Gao, Peijun; Liu, Jiajie; Zhang, Biao; Tao, Guowei (Frontiers in Oncology, 2025)
Benign notochord cell tumor (BNCT) in the bilateral lungs is exceedingly rare. This report details a case of a male patient diagnosed with primary bilateral lung BNCTs and concurrent sacral tumors. As part of a routine health check-up, a chest CT revealed suspicious nodules in both lungs. We performed a thoracoscopic wedge resection of the nodules on him. The postoperative pathological findings combined with CT and clinical manifestations confirmed BNCT. Post-operatively, considering that BNCT commonly occurs in the axial skeleton, we conducted an examination of the spine. Spinal CT and MRI revealed suspicious sacral lesions in the S3 to S5 vertebrae, necessitating further investigation and continuous follow-up monitoring. The simultaneous occurrence of primary multifocal pulmonary BNCTs coexisting with sacral tumors has never been reported before. Fully taking into account potential associations with other diseases, careful follow-up and a comprehensive diagnostic approach are essential for patients with pulmonary nodules.